China 2002: WTO entry and world recession - Garnaut, Ross (ANU Press, 2012)
In 2002 China enters the WTO. Long awaited by the world's trading economies, it now comes in a year of global recession. What effect will China's entry into the WTO have at a difficult time? The rapid expansion of China's trade has required large adjustment in its trading partners, and the expansion and adjustment will accelerate with WTO entry. The internal adjustment pressures in China from WTO entry are also immense. Recently dubbed Australia's Ambassador to the region by Rowan Callick of the Financial Review, Ross Garnaut was Australia's ambassador to China through an earlier exciting period when China took its first major steps towards opening to international trade and investment. He was instrumental in the development of China's thinking about the WTO. Ross Garnaut is Chairman of the China Economy and Business Program at The Australian National University. Australian members of the Program and their associates gather each year for the China Update. Ligang Song is leading authority on the internationalisation of the Chinese economy and on the development of the private sector in China. He has worked at Peking University and People's University in Beijing and at the International University in Tokyo.